PENGARUH SERVICE PERFORMANCE TERHADAP REPEAT PURCHASING MELALUI PERCEIVED VALUE DAN CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING DI ESTHER HOUSE OF BEAUTY SURABAYA - Sylviana Kristian (Jurnal Strategi Pemasaran, 2016)
:  The trend of industy clinic beauty is growing rapidly in many parts of the world, especially in Indonesia.  Motives women to use the clinic beauty is desire actual ourselves and to satisfy internal needs .Clinic beauty Esther House of beauty is clinic beauty that  having a interaction quality which is a service performance relating to attitude , behaviour , expertise .The problem is to know how to measure a customer satisfaction that will lead to a repeat purchasing .Companies should make a best service performance so the consumer will caught a good of perceived value that will cause a customer satisfaction .This research use questionnaire which spread to one hundred respondents with Partial Least Square (PLS) analysis. The results of this research indicate the significant impact of perceived service performance to repeat purchasing in Esther House of Beauty Surabaya